Hybrid Alginate‐Based Cryogels for Life Science Applications1. Issue 11 (29th August 2016) - Barros, Alexandre; Quraishi, Sakeena; Martins, Marta; Gurikov, Pavel; Subrahmanyam, Raman; Smirnova, Irina; Duarte, Ana Rita C.; Reis, Rui L.
Abstract: This work presents a novel route toward porous scaffolds for tissue engineering and regenerative medicine (TERM) applications. Hybrid cryogels with gelatin, gellan gum, carboxymethylcellulose, and lignin were prepared by a two‐step process. Textural properties of the cryogels were analyzed by SEM and micro‐computed tomography. The results indicated that rapid freezing retained sample shape and yielded macroporous materials. The mechanical properties of the cryogels were characterized in compression mode. Cytotoxicity studies indicated that the hybrid‐alginate cryogels did not present cytotoxicity and have the potential to be used in TERM. Abstract : Sodium alginate is known as a good precursor in the hydrogel production for tissue engineering and regenerative medicine applications. Non‐cytotoxic alginate‐based cryogels are produced by carbon dioxide induced gelation and freeze‐drying and characterized for tissue engineering and regenerative medicine applications.